PENINGKATAN KREATIVITAS ANAK MELALUI KEGIATAN BERMAIN FINGER PAINTING PADA ANAK USIA DINI KELOMPOK B PAUD AISYIYAH III KOTA BENGKULU - Levi Sartika; Nina Kurniah; Wembrayarli Wembrayarli (Jurnal Ilmiah POTENSIA, 2018)
The purpose of this research is to increase the creativity of children through playing finger painting activities at early childhood group B PAUD Aisyiyah III city Bengkulu. This study is a classroom action research conducted 2 cycles of the first cycle conducted 3 meetings and cycle conducted 3 meetings. The subjects of this study were 10 children consisting of 6 girls and 4 boys. Data collection techniques in this study is observation, with data analysis techniques using the average. The results of this study prove that the improvement of children's creativity through playing finger painting can be improved through finger painting activities from the research results obtained, it is recommended for teachers to improve children's creativity by applying finger painting activities for researchers further expected research on children's creativity finger painting learning activities with other aspects